Antibacterial Efficacy and Healing Potential of Honey from Different Zones in Nigeria on Diabetic-Induced Wound Infection in Wistar Rats - Agbagwa, Obakpororo Ejiro; Ekeke, Chimezie; Israel, Precious Chidinma (International Journal of Microbiology, 2022)
There is an increase in drug-resistant strains causing infection, thus making available therapeutics less effective. As resistance increases, modern medicine focuses on the antibacterial potential of natural products, which can aid in wound healing. The present study determined Nigeria honey’s antibacterial efficacy in treating diabetes-induced wound infections in Wistar albino rats. 54 Wistar rats randomly divided into 9 groups of 6 each were used for the study: group I (negative control, no treatment), group II (positive control, diabetes without treatment), group III (diabetes treated with 1% silver sulfadiazine), and groups IV–IX (diabetes treated with different honey samples). Physiochemical analysis and microbiological and antibacterial activity of the honey samples were determined. The treatments were carried out for 17 days, and wound contraction, malondialdehyde (MDA) levels, and catalase activity were measured. Results obtained showed that the most effective honey was DCH (21.5 ± 2.12), followed by HBP + M (15 ± 2.12) and TRB, JS, and HBP (13 ± 2.8; 13 ± 1.41; 13.5 ± 0.71) for antibacterial activity on Staphylococcus aureus. Microbiologically, no coliform was detected in all the samples, confirming the honey’s quality. The amount of lipid peroxidation was raised in the diabetic group with no treatment, 1% silver sulfadiazine group, and JS group, while no significant reduction was observed in other groups. Differences in wound contraction were significantly notable on various days of measurement, day 3 (p<0.002), day 6 (p<0.046), and day 9 (p=0.00). The catalase level in the different treatment groups increased significantly (p<0.05), implying an antioxidant potential of the different honey samples except for Jos honey. The study concludes that honey infused with moringa was faster and more efficient in healing diabetic wounds than other honey samples and silver sulfadiazine.